First finding of live specimens of non-native copepod Calanus finmarchicus (Gunnerus, 1770) in the Sea of Marmara - Leonid Svetlichny; Melek İşinibilir; Ahmet Erkan Kıdeyş (Aquatic Sciences and Engineering)
In April of both 2018 and 2019, one specimen each time of live Calanus finmarchicus adult females was found during collections of zooplankton samples near Sivri Ada in the Sea of Marmara. This was the first observation of live C. finmarchicus ( a native species of northern Atlantic waters) in the eastern Mediterranean Sea. This morphological study illustrates the similarity of C. finmarchicus specimens found in the Sea of Marmara with existing illustrations and descriptions of this species. It also shows the clear differences between this species and Calanus helgolandicus specimens collected during the same or earlier periods from the Marmara Sea. Transportation of C. finmarchicus to the Sea of Marmara is possible either via the lower current from the Aegean Sea or through the ballast waters of vessels. In any case, the occurrence of C. finmarchicus as a cold-water species in the Sea of Marmara is striking and attracts further investigations.